Model Manajemen Kepemimpinan di Sekolah Inklusif Berbasis Kearifan Lokal (Studi Kasus di SDN 31 Mataram) - Mardiana; Istilam; Samsul Hadi Hidayatullah; Azkar Nawawi; Bq. Izwana (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to examine how leadership management based on local wisdom is implemented in inclusive schools. The research employed a qualitative approach with a case study design. The subjects of this study included inclusive classroom teachers, special assistant teachers, principals, parents, and students with special needs. The findings revealed that leadership adopting local wisdom values such as “mutual learning, compassion, and care” was successful in creating an inclusive, harmonious, and enjoyable school culture. According to Hasim Asyari, being a leader in an inclusive school presents many challenges, especially in communities that have not fully accepted diversity. However, schools that involve traditional community leaders in educational decision-making processes are able to harmoniously bridge the interests of schools and society. In addition, the principal regularly updates school programs by identifying available resources, implementing local wisdom-based outing class activities, and providing inclusive education training for teachers so that the implementation of inclusive learning can run more effectively and optimally.